Cultivating Victory: The Women's Land Army and the Victory Garden Movement - Cecilia Gowdy-Wygant (University of Pittsburgh Press, 2013)
Throughout the twentieth century, the seeds of victory were sown on farms, vacant lots, in backyards, rooftops, and window boxes. Intentionally selected, meticulously planted, and carefully harvested, these seeds provided food in times of scarcity and a political ideological focus for warring nations. While allied nations shared agricultural strategies, women across three continents shared common goals of liberation, survival, and adventure. As the U.S. and British governments used propaganda and agricultural programs to cultivate both victory and identity, national and international womenâ€™s organizations promoted womenâ€™s place and space within the farm labor force and society through waged farm work. Regardless of national intent and the programs participated in, women who cultivated the land during wartime not only cultivated victory, but also participated in spreading a new political and social culture of abundance focused on the production and distribution of food.1 For both nations, gardening was a cultural statement about national iden-tity. For the English, ornamental gardens were part and parcel of the expression of leisure; families expressed their wealth and stature in society through the elaborate ornamental plants and design of the landscape. For many of Englandâ€™s elite, garden parties were the center of social gatherings, and the elaborate gardens were as much a part of their homes as the dining halls or salons. The â€œEnglish gardenâ€ as it became known around the world, was a place of natural splendor where the elite took time to contemplate, socialize and, as the decades passed, even to organize reform movements. For those of lesser means and stature, gardens were the bridge between the middle class and the elite. Knowledge of ornamental gardening was seen as a genteel trait, as opposed to farm labor, which carried with it a stigma of peasant labor and strife. Thus garden training for women focused more heavily on flower cultivation and garden design rather than nutritive needs of the nation, and many saw this training as preparation for a life of leisure. Though many English women tended to kitchen gardens where they produced basic foods for their families, womenâ€™s magazines and journals of the day focused on the aesthetic nature of those gardens rather than on the labor involved in them or the importance of the production of food. The national focus on these small food-based gardens began to change, however, as wartime food shortages demanded a shift away from the aesthetic to the utilitarian.